Ethernet Communication Design with Service Oriented Architecture (SOA) - Aastha (TIET, 2019)
The thesis describes how Ethernet Communication design can be created with Service Oriented Architecture using SOME/IP protocol which is defined by AUTOSAR. To define SOA, an ADAS use case has been taken for which various services as per the protocol has been defined, these services are then mapped to ECU’s which would be providing and consuming these services. Also the sockets as per the TCP/IP protocol has been defined over which the data contained in the services will be sent on the network. All the above mentioned parameters have been implemented using an E/E architecture tool which was only used to define CAN database, but in this I have proposed how an AUTOSAR compliant architecture on Ethernet can be created. Also in this work, I have shown how diagnostics can be done for different Ethernet using DOIP protocol which will be used in the coming next generation architectures of the vehicles. An ARXML file which is AUTOSAR 4.3.0 has been exported in the form of system extract, ECU extract, software component extract which can be fed to AUTOSAR compliant toolchains to build the software for the purposed use case.
Keywords: Ethernet Communication design; Service Oriented Architecture